Diverse ent-kaurane diterpenoids from Isodon henryi. (12th October 2022) - Cheng, En; Chi, Jun; Li, Yi-Xiao; Zhang, Wei-Jin; Huang, Na; Wang, Zhi-Min; Dai, Li-Ping; Xu, Er-Ping
Graphical abstract: Highlights: Diverse ent -kaurane diterpenoids, including two new ones (1 –2 ) and one new natural one (3 ), were isolated from Isodon henryi . Isohenolide A (1 ) was a rare 6, 8‑cyclo ent -kaurane containing an unprecedented 11, 15-lactone group, and possessed a 6/5/6/6/6/6 ring system. Their structures were confirmed by comprehensive UV, IR, HRESIMS, NMR analyses and ECD calculations. A biosynthetic pathway of compound 1 was proposed. Abstract: Phytochemical investigation of Isodon henryi led to the isolation of two new diterpenoids, isohenolides A-B (1 –2 ), one new natural diterpenoid (3 ) and thirteen known ones (4 –16 ). These diterpenoids showed various ent -kaurane skeletons, in which isohenolide A (1 ) was a rare 6, 8‑cyclo ent -kaurane containing an unprecedented 11, 15-lactone group, and possessed a 6/5/6/6/6/6 ring system. Their structures were confirmed by comprehensive UV, IR, HRESIMS, NMR analyses and ECD calculations. Most compounds were also screened for anti-inflammatory actions on LPS-induced RAW 264.7 cells, and compounds 8 and 16 exhibited stronger NO inhibition.